Persepsi Masyarakat Terhadap Perkawinan Multietnis Di Pekon Pura Wiwitan Kabupaten Lampung Barat - Susiati .; Yunisca Nurmalisa; Ana Mentari; Devi Sutrisno Putri; Rohman . (CV. ITTC INDONESIA, 2026)
This study aims to describe community perceptions of multiethnic marriages and analyze their impact on the formation of civic disposition in Pura Wiwitan Village, West Lampung Regency. The research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving multiethnic couples, community leaders, and village officials. Data analysis included data reduction, data display, and conclusion drawing. The results indicate that multiethnic marriages occur due to intense social interaction and proximity among ethnic groups. Community perceptions vary, with younger generations being more open than older generations who still strongly uphold traditional values. Multiethnic marriages have a positive impact on civic disposition, including tolerance, mutual respect, cultural adaptation, and unity. Furthermore, multiethnic families serve as a medium for internalizing civic values through deliberation, cooperation, and respect for social norms.